Rezafungin for Candidemia and Invasive Candidiasis: A Focus on the Pharmaceutical Development, Related Patents, and Prospects - Dr. Abida, (Asian Journal of Pharmaceutics (AJP), 2024)
Infections caused by Candida are extremely dangerous and pose a serious threat to public health. Echinocandins are an important drug class used to combat fungal infections. A new echinocandin, Rezafungin (REZ), has been approved by the United States Food and Drug Administration (USFDA) on March 22, 2023, to treat invasive candidiasis and candidemia. This review article discusses the pharmaceutical development, patent literature, and the future directions of REZ-based therapy for fungal diseases. The literature for this article was obtained from authentic websites (USFDA, Cidara Therapeutics, and clinicaltrial.gov), PubMed, and various free patent databases (Espacenet, Patentscope, and USPTO) utilizing different keywords. REZ was invented by Seachaid Pharmaceuticals, which disclosed its chemical structure in 2012. Later Cidara Therapeutics acquired the patent rights of REZ from Seachaid Pharmaceuticals. REZ provides better patient compliance (once-a-week dosing) and cost-effective treatment than other marketed echinocandins. REZ demonstrates low CYP450-associated drug interactions but on limited drugs. The pharmacovigilance studies will provide more details of the pharmacokinetic properties, interaction (drug, food, and disease), and use in the special population (children, elderly, pregnant, and lactating women). Echinocandin, including REZ, is effective against many species of Candida. Drug-resistance development has been observed among the drugs of the echinocandin class. This issue must be considered while using REZ. The patent literature of REZ revealed some important REZ-based inventions. The patent literature of the REZ is likewise lacking. The authors predict a promising future for creating numerous patented inventions based on REZ.